Efektifitas Promosi Kesehatan Perawatan Payudara Selama Kehamilan Dengan Ketrampilan Ibu Hamil Di Puskesmas Duono - Yanasein, Yanasein; Ilmiah, Widia Shofa; Sulistiyah, Sulistiyah (NHM PRESS, 2024)
The condition of pregnancy makes changes to the skin, and changes to the breasts. Breast care during pregnancy is an important part that must be considered in preparation for breastfeeding the baby and improving blood circulation Providing breastfeeding education to pregnant women allows mothers to obtain information about lactation preparation and increase knowledge and change maternal behavior about breast care during pregnancy. The purpose of this study is to determine the effectiveness of health promotion about breast care on the skills of pregnant women at the Duono Health Center. The type of research is experimental research (quasi experimental designs) with one group pretest-posttest research design. The population in this study is 16 pregnant women in the second and third trimesters and the sample in this study is 16 pregnant women in the second and third trimesters using the total sampling technique. The results of the statistical test using the wilcoxon signed rank test analysis obtained a significance result P = 0000 (<0.005). The conclusion of this study is that health counseling on breast care is effective in increasing the knowledge of pregnant women at the Duono Health Center. The suggestion from this study is that pregnant women can be more active in participating in pregnant women's classes and counseling held by village midwives or health centers